Comparative efficacy and safety of non-pharmacological interventions as adjunctive treatment for vascular dementia: a systematic review and network meta-analysis - Yi, Yunhao; Qu, Yiwei; Lv, Shimeng; Zhang, Guangheng; Rong, Yuanhang; Li, Ming (Frontiers in Neurology, 2024)
The incidence of vascular dementia (VaD) is steadily rising annually, significantly impacting the mental well-being and overall quality of life of the elderly, and imposing substantial economic burdens on families and society. In recent years, non-pharmacological therapies as supplementary treatments for VaD have garnered significant attention and have been extensively utilized in clinical settings. Consequently, a network meta-analysis (NMA) was conducted by us to assess the effectiveness of various non-pharmacological therapies in the management of VaD.We systematically searched seven databases from their inception up to January 2024 to identify randomized controlled trials focusing on non-pharmacological interventions for the treatment of VaD. The methodological quality and risk of bias were rigorously assessed utilizing the RoB 2.0 evaluation tool. The NMA was performed using R software and STATA 14 software, adhering to frequentist theory principles. Additionally, sensitivity analysis, meta-regression analysis, and funnel plot were conducted to assess the stability, heterogeneity, and publication bias, respectively.The NMA included 91 eligible studies involving 7657 patients. The NMA results indicated that in terms of improving Mini-Mental State Examination (MMSE), the following nonpharmacological interventions ranked higher based on P-value: acupuncture_moxibustion_ conventional treatment (ACUP_MB_CT) (P-score = 0.95; pooled mean difference (95% CI): 5.09 (3.82; 6.36)), fastigial nucleus stimulation_CT (FNS_CT) (0.87; 4.51 (2.59; 6.43)),